Ocular Pharmacokinetics of Naringenin Eye Drops Following Topical Administration to Rabbits - Lin, Junli (J Ocul Pharmacol Ther, 2015)
Purpose: To investigate the ocular pharmacokinetics of 1% naringenin eye drops following topical administration to rabbits. Methods: One drop (50 μL) of 1% naringenin eye drops was instilled into both eyes of each rabbit. The animals were sacrificed at predetermined intervals after dosing, and ocular tissues and plasma were then collected. Concentrations of naringenin were analyzed using specific electrospray ionization liquid chromatography-tandem mass spectrometry method, which is proved to be sensitive, specific, precise, and suitable for determination of naringenin in ocular tissues and plasma of rabbits. Results: Ocular exposure to naringenin, based on AUC((0−t)), was highest in cornea, followed by aqueous humor, retina, and vitreous body. The C(max) of naringenin in cornea, aqueous humor, vitreous body, and retina were 67945.30±4109.34 ng/g, 1325.69±239.34, 160.52±38.78 ng/mL, and 1927.08±660.77 ng/g at 0.083, 0.75, 0.083, and 0.083 h after topical administration, respectively. The half-lives for these tissues were 9.37, 0.65, 1.17, and 4.62 h, respectively. There was no significant difference between free naringenin and total naringenin in plasma based on C(max) and T(max). C(max) of total naringenin in plasma at 0.083 h was 35.12±0.54 ng/mL. Conclusions: Measurable concentrations of naringenin were achieved in ocular tissues after topical application in rabbits. Topical instillation of naringenin may be an effective approach in the treatment of posterior section diseases.